DILEMA INDONESIA DALAM RATIFIKASI FRAMEWORK CONVENTION ON TOBACCO CONTROL TERHADAP INDUSTRI ROKOK NASIONAL - Achmad Ravie; Havidz Ageng Prakoso; Haryo Prasodjo (Universitas Tribhuwana Tunggadewi, 2023)
Thispaper discusses Indonesia's dilemma regarding the ratification of the Framework Convention on Tobacco Control (FCTC). The purpose of this study is to understand more about the dilemma of the Ratification of the International Treaty Convention on Tobacco Control related to the threat of Indonesian state income from cigarette taxes for Indonesia. Data collection techniques in this study using library research (library research). The analysis technique in this study uses inductive analysis techniques. The Framework Convention on Tobacco Control was issued as one of the efforts of the international community to control tobacco consumption. The Indonesian state itself, which is actively participating in the formulation of the Framework Convention on Tobacco Control agreement as a drafting committee, has not yet been willing to ratify the Framework Convention on Tobacco Control. In fact, Indonesia is the only country in the Asia Pacific region that is not yet willing to ratify this agreement. Therefore, various questions arise as to why the Indonesian government is not yet willing to ratify this treaty convention.AbstrakPenelitian ini membahas dilema Indonesia terkait ratifikasi Framework Convention on Tobacco Control (FCTC). Tujuan penelitian ini yaitu untuk memehami lebih lanjut mengenai dilema Ratifikasi Konvensi Perjanjian Internasional Masalah Pengendalian Tembakau terkait ancaman pendapatan negara Indonesia dari pajak rokok bagi Indonesia. Teknik pengumpulan data dalam penelitian ini menggunakan studi pustaka (library research). Teknik analisa pada penelitian ini menggunakan teknik analisa induktif. FCTC dikeluarkan sebagai salah satu upaya dari masyarakat internasional guna untuk pengendalian konsumsi tembakau. Negara Indonesia sendiri yang aktif ikut serta dalam perumusan perjanjian FCTC sebagai drafting committee, sampai dengan saat ini belum juga bersedia untuk meratifikasi FCTC. Bahkan negara Indonesia menjadi negara satu-satunya di kawasan Asia Pasifik yang belum bersedia untuk meratifikasi perjanjian ini. Faktor penyebab dilema yang dihadapi Indonesia yaitu Industri rokok memberikan dampak positif bagi pendapatan Negara tetapi memiliki dampak buruk terhadap kesehatan masyarakat.